Analisis Kualitas Produk Tahu dalam Perspektif Itqān dan Standar Halalan Thayyib (Studi Kasus pada Pabrik Tahu di Kecamatan Tanete Riattang Barat) - Eva Sri Yulianingsi; Aksi Hamzah; Muhammad Ardi (IKRAITH-EKONOMIKA, 2026)
This study examines the quality of tofu products in Tanete Riattang Barat District from the perspective of the principle of itqān (work professionalism in Islam) and the standards of halalan thayyiban. The objectives of the study are: (1) to analyze the tofu production process from the perspective of itqān; (2) to examine the implementation of halalan thayyiban standards in the production process; and (3) to identify the challenges and obstacles faced by tofu factories. The study uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observations, and documentation. The informants consist of the owners and workers of the tofu factories. Data analysis refers to the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions and verification. The results show that the application of the itqān principle has been carried out fairly well, reflected in diligent work, meticulous production processes, efficient division of labor, and the moral awareness of business actors. The implementation of halalan thayyiba standards